Composite ceramic aerogel and preparation method thereof
By synthesizing composite ceramic aerogels with low-cost carbon and silicon sources and performing heat treatment at high temperatures, the problem of service temperature limit of ceramic aerogels in high temperature scenarios is solved, and low-cost, large-scale preparation and excellent high temperature resistance and oxidation resistance.
Patent Information
- Application Number
- CN202411728720.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-18
AI Technical Summary
Existing ceramic aerogels have problems such as service temperature limitation, complex preparation process, high cost and difficulty in achieving large-scale production in high-temperature scenarios.
The low-cost, easy-to-acquire carbon source and silicon source are used as the precursors for the synthetic composite ceramic aerogel. The composite ceramic aerogel is formed through carbon-heat reduction reaction, and heat treatment is carried out in an inert or nitrogen-containing atmosphere to prepare the anti-resistance. Composite ceramic aerogel with an oxidation temperature up to 1600℃.
The low-cost and large-scale preparation of composite ceramic aerogels is achieved, with excellent high temperature resistance and oxidation resistance, and it also gives composite ceramic aerogels high compression rebound and bending resistance.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite ceramic aerogels, and in particular relates to a composite ceramic aerogel and a preparation method thereof. Background Art
[0002] So far, a variety of aerogels have been reported, including silicon dioxide, silicon carbide, carbon nanotubes, graphene and polymer aerogels. Among them, ceramic aerogels have become new materials with great potential due to their ultra-low density, ultra-high porosity, ultra-low thermal conductivity and high temperature resistance. Their unique properties make them have important application value in the fields of thermal insulation, catalyst barrier, energy storage, piezoelectricity and sensors.
[0003] At present, ceramic aerogels are mainly divided into two categories: oxide ceramic aerogels and non-oxide ceramic aerogels (such as nitrides, carbides, borides, etc.). Due to the high-temperature crystallization embrittlement and high-temperature structural collapse of oxide aerogels, their service temperature is difficult to exceed 1000°C. In contrast, among non-oxide ceramic aerogels, silicon nitride aerogels and silicon carbide aerogels exhibit excellent mechanical flexibility and high-temperature resistance, and are very ideal materials.
[0004] At present, the preparation of silicon nitride aerogel and silicon carbide aerogel usually requires the use of complex process flows and expensive raw materials. In addition, the aerogels prepared by them cannot be prepared on a large scale, which greatly limits the practical use of aerogels. For example, the invention patent with publication number CN 112047742 A - a low-cost preparation method for large-size silicon nitride nanobelt aerogel, uses low-cost silicon powder and nitrogen as raw materials to directly synthesize silicon nitride. Although low-cost preparation can be achieved, the size and shape of the prepared samples are limited and cannot meet the actual high-temperature scene. The invention patent with publication number CN110668446 A - a method for preparing high-temperature resistant SiC aerogel discloses a silicon carbide aerogel, in which a hydrogel is prepared by hydrolysis and condensation of methyl orthosilicate, Span-20, and magnesium powder, and a crude silicon carbide aerogel product is prepared by aging, drying, and firing, and then impurities are removed by hydrofluoric acid etching to obtain SiC aerogel. The preparation method of the silicon carbide aerogel requires the use of hydrofluoric acid etching, which is dangerous to operate, the process is cumbersome and complicated, and the efficiency is low, so it is not suitable for large-scale preparation of aerogels. The invention patent with publication number CN 112537961 A - a preparation method of a polymer precursor ceramic aerogel, which uses a sol-gel method to obtain a precursor wet gel, and then obtains a block silicon carbide precursor aerogel by supercritical drying or freeze drying. Although this method can achieve large-scale preparation of aerogels, the supercritical drying or freeze drying process consumes a lot of energy, the preparation cost is high, and it is difficult to achieve low-cost manufacturing. The invention patent with publication number CN 115433012 A - a silicon carbide ceramic aerogel and its preparation method, uses a low-cost silicon powder and silicon dioxide mixture as raw materials to directly synthesize silicon nitride. Although low-cost preparation can be achieved, it requires the use of a hydrothermal method to prepare a graphene oxide precursor skeleton, which greatly increases the difficulty and cost of preparation. Summary of the invention
[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a composite ceramic aerogel and a preparation method thereof, which has low cost and is conducive to large-scale production. The ceramic aerogel has an oxidation resistance temperature of up to 1600°C and is suitable for high-temperature scenarios.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention provides a method for preparing a composite ceramic aerogel, comprising the following steps: Preparing a precursor sol, then adding a metal catalyst, and mixing evenly to obtain a mixed sol; The ceramic fiber preform is immersed in the mixed sol, taken out and dried to form a mixed fiber preform, and then subjected to high-temperature heat treatment in an inert atmosphere or a nitrogen-containing atmosphere to obtain a composite ceramic aerogel.
[0007] The preparation process of the precursor sol is as follows: The carbon source and the silicon source are dispersed in a solvent to prepare a precursor sol.
[0008] In one embodiment, the carbon source is one or more of carbon powder, phenolic resin, epoxy resin, polypropylene resin, melamine, polyurethane, and graphene.
[0009] In one embodiment, the silicon source is one or more of silicon dioxide powder, silicon monoxide powder, ethyl orthosilicate, methyl orthosilicate, siloxane, polycarbosilane, and polynitrogen silane.
[0010] In one embodiment, the solvent is one or more of ethanol, ethylene glycol, methanol, butanol, isopropanol, acetone, toluene, xylene, n-hexane, cyclohexane, ether, acetonitrile, dichloromethane, and chloroform.
[0011] In one embodiment, the mass ratio of the carbon source, the silicon source and the solvent is (1-50): (0.5-30): (10-100).
[0012] In one embodiment, the metal catalyst is one or more of a platinum catalyst, a palladium catalyst, a copper catalyst, and a nickel catalyst.
[0013] In one embodiment, the amount of the metal catalyst added is 0.01 wt% to 0.5 wt% of the mass of the silicon source.
[0014] In one embodiment, the ceramic fiber preform is one or more of a glass fiber preform, a quartz fiber preform, an alumina fiber preform, a mullite fiber preform, a high-silica glass fiber preform, a zirconium oxide fiber preform, a silicon carbide fiber preform, an aluminum silicate fiber preform, a basalt fiber preform, a zirconium silicate fiber preform, a rock wool fiber preform, and a silicon nitride fiber preform.
[0015] In one embodiment, the inert atmosphere is one or more of argon and helium.
[0016] In one embodiment, the nitrogen-containing atmosphere is one or more of nitrogen, ammonia or ethylenediamine.
[0017] In one embodiment, the high temperature heat treatment is performed at a temperature of 1250°C to 1800°C.
[0018] The present invention also provides a composite ceramic aerogel prepared by the preparation method of the composite ceramic aerogel. The composite ceramic aerogel prepared in an inert atmosphere mainly comprises silicon carbide aerogel, and the composite ceramic aerogel prepared in a nitrogen-containing atmosphere mainly comprises silicon nitride aerogel.
[0019] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a composite ceramic aerogel and a preparation method thereof. Low-cost and easily available carbon source and silicon source are used as precursors for synthesizing the composite ceramic aerogel, and a carbon thermal reduction reaction is utilized to form the composite ceramic aerogel. The composite ceramic aerogel is low in cost and is conducive to large-scale production.
[0020] Further, the main structure of the composite ceramic aerogel is silicon nitride aerogel or silicon carbide aerogel, and the silicon nitride aerogel or silicon carbide aerogel will spontaneously form a dense oxide film during use, which effectively improves the high-temperature oxidation resistance of the composite ceramic aerogel. The oxidation resistance temperature of the ceramic aerogel can reach 1600°C. In actual use, the oxide film will form a molten silica liquid, which can fill the partially exposed area, thereby better protecting the main structure of the composite ceramic aerogel, silicon nitride or silicon carbide. In addition, the structural components constituting the composite ceramic aerogel are one-dimensional silicon nitride nanowires and two-dimensional silicon nitride nanobelts or one-dimensional silicon carbide nanowires. Compared with granular and nanosheet structural components, these large aspect ratio nanowires and nanobelts have higher mechanical deformation capabilities, giving the composite ceramic aerogel excellent compression rebound and anti-bending capabilities. Therefore, the composite ceramic aerogel prepared by the present invention has the advantages of higher temperature resistance, oxidation resistance, and low cost and large-scale preparation. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is an optical photograph of the composite ceramic aerogel prepared in Example 1 of the present invention; Figure 2 This is a SEM photo of the composite ceramic aerogel prepared in Example 1 of the present invention; Figure 3 The stress-strain curve of the composite ceramic aerogel prepared in Example 1 of the present invention; Figure 4 XRD of the composite ceramic aerogel prepared in Example 1 of the present invention; Figure 5 This is the EDS spectrum of the composite ceramic aerogel prepared in Example 1 of the present invention, wherein (a) shows the N element and (b) shows the Si element; Figure 6 This is a photo of the composite ceramic aerogel prepared in Example 1 of the present invention being sprayed under a butane flame; Figure 7 This is a comparison of macroscopic photographs of the composite ceramic aerogel prepared in Example 1 of the present invention after heat treatment in an oxygen environment at 1600°C for 30 minutes, wherein (a) is before heat treatment, and (b) is after heat treatment; Figure 8 This is a SEM photo of the composite ceramic aerogel prepared in Example 2 of the present invention; Fig. 9This is the EDS energy spectrum of the composite ceramic aerogel prepared in Example 2 of the present invention, wherein (a) shows the C element and (b) shows the Si element. DETAILED DESCRIPTION
[0022] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0023] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0024] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0025] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0026] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0027] The present invention provides a composite ceramic aerogel and a preparation method thereof, the preparation method comprising the following steps: preparing a precursor sol, then adding a metal catalyst, mixing evenly, and obtaining a mixed sol; The ceramic fiber preform is immersed in the mixed sol, taken out and dried to form a mixed fiber preform, and then subjected to high temperature heat treatment at 1250°C to 1800°C in an inert atmosphere or a nitrogen-containing atmosphere to obtain a composite ceramic aerogel.
[0028] The main body of the composite ceramic aerogel prepared in an inert atmosphere is silicon carbide aerogel, and the main body of the composite ceramic aerogel prepared in a nitrogen-containing atmosphere is silicon nitride aerogel.
[0029] The specific dosage and process conditions of the above preparation method are as follows: The preparation process of the precursor sol is as follows: The carbon source and the silicon source are dispersed in a solvent to prepare a precursor sol.
[0030] The carbon source can be one or a combination of carbon powder, phenolic resin, epoxy resin, polypropylene resin, melamine, polyurethane, and graphene. The silicon source can be one or a combination of silicon dioxide powder, silicon monoxide powder, ethyl orthosilicate, methyl orthosilicate, siloxane, polycarbosilane, and polynitrogen silane.
[0031] Among them, the mass ratio of carbon source, silicon source and solvent is (1~50):(0.5~30):(10~100).
[0032] The metal catalyst can be one or a combination of platinum catalyst, palladium catalyst, copper catalyst and nickel catalyst.
[0033] The added amount of the above metal catalyst is 0.01wt%~0.5wt% of the mass of the silicon source.
[0034] The above-mentioned ceramic fiber preform can be: a glass fiber preform, a quartz fiber preform, an alumina fiber preform, a mullite fiber preform, a high-silica glass fiber preform, a zirconium oxide fiber preform, a silicon carbide fiber preform, an aluminum silicate fiber preform, a basalt fiber preform, a zirconium silicate fiber preform, a rock wool fiber preform, a silicon nitride fiber preform, or a composite of one or more of them.
[0035] The inert atmosphere may be one or a combination of argon and helium; the nitrogen-containing atmosphere may be one or a combination of nitrogen, ammonia or ethylenediamine.
[0036] like Figures 1 to 4 As shown, the main component of the composite ceramic aerogel prepared by the above preparation method is silicon nitride aerogel or silicon carbide aerogel; the structural components of the silicon nitride aerogel are mainly one-dimensional silicon nitride nanowires and two-dimensional silicon nitride nanobelts, and the main components of silicon nitride are N and Si. Figure 8 and 9 As shown, the structural components of silicon carbide aerogel are mainly one-dimensional silicon carbide nanowires, and the main components of silicon carbide are C and Si.
[0037] The composite ceramic aerogel has a low thermal conductivity of 0.02-0.5 W / mk; Figure 5 As shown, the composite ceramic aerogel has excellent high temperature resistance and its appearance does not change significantly when sprayed in a butane flame at 1300°C.
[0038] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0039] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0040] Embodiment 1: Carbon powder, tetraethyl orthosilicate and ethanol are prepared into a precursor sol in a mass ratio of 1:0.5:10, and then a platinum catalyst with a mass percentage of 0.01wt% of the tetraethyl orthosilicate is added and mixed evenly to obtain a mixed sol. A silicon nitride fiber preform is immersed in the sol, taken out and dried to form a mixed fiber preform, and then heat treated at 1250°C in an ammonia atmosphere to obtain a composite ceramic aerogel.
[0041] The density of the prepared composite ceramic aerogel is 50 mg / cm 3 , the thermal conductivity at room temperature is 0.082 W / mk. Figure 1 It can be seen that the composite ceramic aerogel is light white three-dimensional block. Figure 2 It can be seen that the composite ceramic aerogel is mainly composed of silicon nitride nanowires and silicon nitride nanobelts. Figure 3 It can be seen that the composite ceramic aerogel has excellent mechanical rebound properties. Figure 4 It can be seen that the composite ceramic aerogel is composed of highly crystalline silicon nitride. Figure 5 It can be seen that the element composition of the composite ceramic aerogel includes N and Si. Figure 6 It can be seen that the appearance of the composite ceramic aerogel does not change significantly when it is sprayed in a butane flame at 1300 °C. Figure 7 It can be seen that the volume of the composite ceramic aerogel does not shrink significantly after heat treatment at 1600 ℃ in an oxygen environment for 30 min.
[0042] Embodiment 2: Polycarbosilane, silicon monoxide powder and ethylene glycol are prepared into a precursor sol in a mass ratio of 50:30:100, and then a palladium catalyst of 0.5wt% of the mass of the silicon monoxide powder is added and mixed evenly to obtain a mixed sol. A silicon carbide fiber preform is immersed in the sol, taken out and dried to form a mixed fiber preform, and then heat treated at 1800°C in an ethylenediamine atmosphere to obtain a composite ceramic aerogel.
[0043] The density of the prepared composite ceramic aerogel is 38 mg / cm 3 , the thermal conductivity at room temperature is 0.048W / mk. Figure 8 It can be seen that the composite ceramic aerogel is mainly composed of silicon carbide nanowires. Fig. 9 It can be seen that the elemental composition of the composite ceramic aerogel includes C element and Si element.
[0044] Embodiment 3: Phenolic resin, tetraethyl orthosilicate and methanol are configured into a precursor sol in a mass ratio of 50:0.5:20, and then a copper catalyst of 0.2wt% of the mass of tetraethyl orthosilicate is added and mixed evenly to obtain a mixed sol. A glass fiber preform is immersed in the sol, taken out and dried to form a mixed fiber preform, and then heat treated at 1350°C in a nitrogen atmosphere to obtain a composite ceramic aerogel.
[0045] Embodiment 4: Epoxy resin, methyl orthosilicate and butanol are prepared into a precursor sol in a mass ratio of 1:30:50, and then a nickel catalyst with a mass percentage of 0.2wt% of methyl orthosilicate is added and mixed evenly to obtain a mixed sol. A quartz fiber preform is immersed in the sol, taken out and dried to form a mixed fiber preform, and then heat treated at 1750°C in a nitrogen atmosphere to obtain a composite ceramic aerogel.
[0046] Embodiment 5: Melamine, siloxane and isopropanol are configured into a precursor sol in a mass ratio of 1:30:60, and then a platinum catalyst with a mass percentage of 0.1wt% of the siloxane is added and mixed evenly to obtain a mixed sol. An alumina fiber preform is immersed in the sol, taken out and dried to form a mixed fiber preform, and then heat treated at 1350°C in an argon atmosphere to obtain a composite ceramic aerogel.
[0047] Embodiment 6: Polyurethane, polycarbosilane and acetone are prepared into a precursor sol in a mass ratio of 1:20:60, and then a platinum catalyst of 0.1wt% of the mass of polycarbosilane is added and mixed evenly to obtain a mixed sol. A mullite fiber preform is immersed in the sol, taken out and dried to form a mixed fiber preform, and then heat-treated at 1350°C in an ammonia atmosphere to obtain a composite ceramic aerogel.
[0048] Embodiment 7: Graphene, polynitrogen silane and toluene are configured into a precursor sol in a mass ratio of 1:0.5:20, and then a platinum catalyst of 0.1wt% of the mass of polynitrogen silane is added and mixed evenly to obtain a mixed sol. A zirconia fiber preform is immersed in the sol, taken out and dried to form a mixed fiber preform, and then heat-treated at 1650°C in an ethylenediamine atmosphere to obtain a composite ceramic aerogel.
[0049] Embodiment 8: Epoxy resin, silica powder and xylene are prepared into a precursor sol in a mass ratio of 1:0.5:30, and then a platinum catalyst with a mass percentage of 0.2wt% of the silica powder is added and mixed evenly to obtain a mixed sol. A silicon carbide fiber preform is immersed in the sol, taken out and dried to form a mixed fiber preform, and then heat treated at 1350°C in a helium atmosphere to obtain a composite ceramic aerogel.
[0050] Embodiment 9: Polypropylene resin, polycarbosilane and n-hexane are configured into a precursor sol in a mass ratio of 1:20:60, and then a platinum catalyst of 0.1wt% of the mass of polycarbosilane is added and mixed evenly to obtain a mixed sol. An aluminum silicate fiber preform is immersed in the sol, taken out and dried to form a mixed fiber preform, and then heat treated at 1300°C in an ammonia atmosphere to obtain a composite ceramic aerogel.
[0051] Embodiment 10: Polyurethane, polycarbosilane and cyclohexane are configured into a precursor sol in a mass ratio of 1:20:60, and then a platinum catalyst of 0.1wt% of the mass of polycarbosilane is added and mixed evenly to obtain a mixed sol. A basalt fiber preform is immersed in the sol, taken out and dried to form a mixed fiber preform, and then heat treated at 1650°C in a helium atmosphere to obtain a composite ceramic aerogel.
[0052] Embodiment 11: Polyurethane, methyl orthosilicate and ether are prepared into a precursor sol in a mass ratio of 1:20:60, and then a platinum catalyst with a mass percentage of 0.1wt% of the mass of methyl orthosilicate is added and mixed evenly to obtain a mixed sol. A zirconium silicate fiber preform is immersed in the sol, taken out and dried to form a mixed fiber preform, and then heat treated at 1350°C in an argon atmosphere to obtain a composite ceramic aerogel.
[0053] Embodiment 12: Polyurethane, polycarbosilane and acetonitrile are configured into a precursor sol in a mass ratio of 1:20:60, and then a platinum catalyst of 0.1wt% of the mass of polycarbosilane is added and mixed evenly to obtain a mixed sol. A rock wool fiber preform is immersed in the sol, taken out and dried to form a mixed fiber preform, and then heat treated at 1450°C in an argon atmosphere to obtain a composite ceramic aerogel.
[0054] Embodiment 13: Polyurethane, polycarbosilane and dichloromethane are prepared into a precursor sol in a mass ratio of 1:20:60, and then a platinum catalyst of 0.1wt% of the mass of polycarbosilane is added and mixed evenly to obtain a mixed sol. A high-silica glass fiber preform is immersed in the sol, taken out and dried to form a mixed fiber preform, and then heat-treated at 1550°C in an ethylenediamine atmosphere to obtain a composite ceramic aerogel.
[0055] Embodiment 14: Polyurethane, polycarbosilane and chloroform are configured into a precursor sol in a mass ratio of 1:20:60, and then a platinum catalyst of 0.1wt% of the mass of polycarbosilane is added and mixed evenly to obtain a mixed sol. A rock wool fiber preform is immersed in the sol, taken out and dried to form a mixed fiber preform, and then heat treated at 1350°C in a nitrogen atmosphere to obtain a composite ceramic aerogel.
[0056] In summary, the composite ceramic aerogel prepared by the present invention has excellent flexibility, thermal insulation and antioxidant properties, and can be prepared at low cost and on a large scale, and has great application potential in thermal insulation fields such as aerospace, high-temperature kilns and fire protection engineering.
[0057] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a composite ceramic aerogel, characterized in that: The following steps are involved: Preparing a precursor sol, then adding a metal catalyst, and mixing evenly to obtain a mixed sol; The ceramic fiber preform is immersed in the mixed sol, taken out and dried to form a mixed fiber preform, and then subjected to high-temperature heat treatment in an inert atmosphere or a nitrogen-containing atmosphere to obtain a composite ceramic aerogel.
2. The method for preparing a composite ceramic aerogel according to claim 1, characterized in that: The preparation process of the above precursor sol is as follows: Dispersing a carbon source and a silicon source in a solvent to prepare a precursor sol; The carbon source is one or more of carbon powder, phenolic resin, epoxy resin, polypropylene resin, melamine, polyurethane, and graphene; the silicon source is one or more of silicon dioxide powder, silicon monoxide powder, tetraethyl orthosilicate, methyl orthosilicate, siloxane, polycarbosilane, and polynitrogen silane; and the solvent is one or more of ethanol, ethylene glycol, methanol, butanol, isopropanol, acetone, toluene, xylene, n-hexane, cyclohexane, ether, acetonitrile, dichloromethane, and chloroform.
3. The method for preparing a composite ceramic aerogel according to claim 2, characterized in that: The mass ratio of the carbon source, the silicon source and the solvent is (1-50): (0.5-30): (10-100).
4. The method for preparing a composite ceramic aerogel according to claim 2, characterized in that: The metal catalyst is one or more of a platinum catalyst, a palladium catalyst, a copper catalyst, and a nickel catalyst.
5. The method for preparing a composite ceramic aerogel according to claim 4, characterized in that: The added amount of the metal catalyst is 0.01wt% to 0.5wt% of the mass of the silicon source.
6. The method for preparing a composite ceramic aerogel according to claim 1, characterized in that: The ceramic fiber preform is one or more of a glass fiber preform, a quartz fiber preform, an alumina fiber preform, a mullite fiber preform, a high-silica glass fiber preform, a zirconium oxide fiber preform, a silicon carbide fiber preform, an aluminum silicate fiber preform, a basalt fiber preform, a zirconium silicate fiber preform, a rock wool fiber preform, and a silicon nitride fiber preform.
7. The method for preparing a composite ceramic aerogel according to claim 1, characterized in that: The inert atmosphere is one or more of argon and helium.
8. The method for preparing a composite ceramic aerogel according to claim 1, characterized in that: The nitrogen-containing atmosphere is one or more of nitrogen, ammonia or ethylenediamine.
9. The method for preparing a composite ceramic aerogel according to claim 1, characterized in that: The temperature of the high temperature heat treatment is 1250°C to 1800°C.
10. A composite ceramic aerogel prepared according to the method for preparing a composite ceramic aerogel according to any one of claims 1 to 9, characterized in that: The main body of the composite ceramic aerogel prepared in an inert atmosphere is silicon carbide aerogel, and the main body of the composite ceramic aerogel prepared in a nitrogen-containing atmosphere is silicon nitride aerogel.
Citation Information
Patent Citations
Preparation method of high temperature resistant SiC aerogel
CN110668446A
Low-cost preparation method of large-size silicon nitride nanobelt aerogel
CN112047742A
Preparation method of polymer precursor ceramic aerogel
CN112537961A
Silicon carbide ceramic aerogel and preparation method thereof
CN115433012A